PRELIMINARY ANALYSIS OF A SET OF SELECTED DENTAL NON-METRIC TRAITS AMONGST SOUTHERN JORDANIANS - Anwar Rahamneh; Ali Al-Zyoud; Firas Al-Soleihat; Mohammad Al-Omosh; Raghda Al-Shamout (Pakistan Oral & Dental Journal, 2020)
The study was done to determine the expression frequency and sexual dimorphism of five dental morphological traits on the permanent dentitions of those living in South Jordanians. Dental stone casts for the dentitions of 380 adult Jordanians (196 females, 184 males; age range = 16-22, mean ages 18.2, St.d = 2.3 years) were studied in 2017. The traits were classified using the Arizona State University dental anthropology system, counted with the individual count method, and dichotomized according to the criteria of Scott & Turner for the purpose of group comparisons. Fisher’s exact test for dichotomized scores was used to assess sexual dimorphism in these traits. Statistically significant sexual dimorphism was found in three out of the five traits: Carabelli’s tubercle/cusp and cusp 5 (metaconule) on UM1 in favor of females, and hypoconulid absence (4-cusped form) on LM1 in favor of males. The expression frequencies of four out of the five traits examined were different from the other non-Middle Eastern Western Eurasian groups, and the differences were in the direction of more trait manifestations amongst the Jordanian group. It was concluded that the dental morphological pattern of South Jordanians showed more trait elaboration than that of non-Middle Eastern Western Eurasian groups.